"Cooperative is an oxymoron!": A polycentric energy transition perspective on distributed energy deployment in the Upper Midwestern United States. (January 2023) - Grimley, Matthew; Chan, Gabriel
Abstract: Load management is the practice of adjusting demand in an electricity system through remote control of—or incentives to operate—grid-edge technologies in alignment with system goals. Although load management functions as a distributed energy resource (DER) and can play a critical role in cost-effective deployment of renewable energy toward economy-wide deep decarbonization, there has been little energy transitions research on how electric grid actors initiate and manage DER deployments over time. We use interviews and archival research to compare case studies of electric cooperatives in the United States, tracing how cooperatives deployed more than 600, 000 load management devices over 70 years. Using polycentricism as a frame, we find that DER deployments comprise common pool resources that are strategically created and negotiated across scales by different centers of decision-making over time. Our findings rebut the assumption that DER deployments are solely the result of policies or markets, showing that DER deployments are instead polycentric acts of cooperation and competition. DER deployments require diverse intermediaries within and across levels of deployment, from policy to users, over many years. We show that polycentric governance that builds vertical coordination across local and regional actors can support broad, deep, and distributed energy transition. Highlights: Electric co-ops have 70 years of experience with distributed energy resources. Distributed energy resources are deployed in polycentric systems. Actors compete and collaborate across scales in energy transition. Intermediating across levels is needed to build coordination across levels.